Reuters Institute digital news report 2014 - Newman, N; Levy, DAL (Reuters Institute for the Study of Journalism, 2014)
The Reuters Institute Annual Digital News Report reveals new insights about digital news consumption based on a representative survey of online news consumers conducted by YouGov. The 2014 report includes 10 countries: the UK, US, Germany, France, Italy, Spain, Finland, Urban Brazil, Japan and Denmark. The 2014 report contains unique data and analysis about the move to mobile, paying for news, social media and more.